Mitochondrial antioxidant SkQ1 decreases inflammation following hemorrhagic shock by protecting myocardial mitochondria - Jia, Bo; Ye, Jingjing; Gan, Lebin; Li, Rui; Zhang, Mengwei; Sun, Diya; Weng, Lin; Xiong, Yufei; Xu, Jun; Zhang, Peng; Huang, Wei; Zheng, Ming; et al. (Frontiers in Physiology, 2022)
Background: Hemorrhagic shock (HS) is a type of hypovolemic shock characterized by hemodynamic instability, tissue hypoperfusion and cellular hypoxia. In pathophysiology, the gradual accumulation of reactive oxygen species (ROS) damages the mitochondria, leading to irreversible cell damage and the release of endogenous damage-associated molecular patterns (DAMPs) including mitochondrial DAMPs (MTDs), eventually triggering the inflammatory response. The novel mitochondria-targeted antioxidant SkQ1 (Visomitin) effectively eliminate excessive intracellular ROS and exhibits anti-inflammatory effects; however, the specific role of SkQ1 in HS has not yet been explicated. Methods and results: A 40% fixed-blood-loss HS rat model was established in this study. Transmission electron microscopy showed that after HS, the myocardial mitochondrial ultrastructure was damaged and the mtDNA release in circulation was increased and the differently expressed genes were significantly enriched in mitochondrial and ROS-related pathways. Mitochondria-targeted antioxidant SkQ1 attenuated the increased ROS induced by HS in myocardial tissues and by oxgen-glucose deprivation (OGD) in cardiomyocytes. Ultrastructurally, SkQ1 protected the myocardial mitochondrial structure and reduced the release of the peripheral blood mtDNA after HS. RNA-seq transcriptome analysis showed that 56.5% of the inflammation-related genes, which altered after HS, could be significantly reversed after SkQ1 treatment. Moreover, ELISA indicated that SkQ1 significantly reversed the HS-induced increases in the TNF-α, IL-6, and MCP-1 protein levels in rat peripheral blood. Conclusions: HS causes damage to the rat myocardial mitochondrial structure, increases mtDNA release and ROS contents, activates the mitochondrial and ROS-related pathways, and induces systemic inflammatory response. The mitochondrial antioxidant SkQ1 can improve rat myocardial mitochondria ultrastructure, reduce mtDNA and ROS contents, and decrease inflammation by protecting myocardial mitochondria, thereby playing a novel protective role in HS.